Changes in health over time in patients with symptoms allegedly caused by their dental restorative materials - Tillberg A, Berglund A, Ma°rell L, Bergdahl J, Eriksson N, Linde´n G, Stenberg B (Blackwell Synergy, 2005)
In Sweden, many patients with symptoms allegedly caused by their dental materials have exchanged their restorations, but the effects of the exchange have been insufficiently investigated.